Incidence of HIV, its predictors and risk factors in children - Goyal, Alok Kumar; Agrawal, Vijay; Thapar, Karuna; Agrawal, Ruchi (International Journal of Contemporary Pediatrics, 2017)
Background: Children mostly acquire HIV (Human immunodeficiency syndrome) infection from their parents. There is need to know the HIV status of their parents, associated risk factors and predictors so as to make effective strategies to prevent this disease and save the coming/future generation from this deadly disease. The objective of the study was to know incidence of HIV, its predictors and risk factors in children. Study Setting: This is a Hospital based observation study conducted in Department of Pediatrics, Govt. Medical College, Amritsar. Methods: In this study, all patients admitted to Pediatrics department, irrespective of presenting complaints were evaluated for presence of any of risk factors/predictors as mentioned in Proforma and those children having any of risk factors/predictors were selected, consent was taken and undergone detailed clinical evaluation and investigations for HIV. Results: Incidence of HIV in all patients admitted to children ward was 1.21% (27/2227) and children who had one or more risk factor or predictor was 6.58% (27/410). Weight loss, Failure to thrive (44.44%), Diarrhoea (37.03%), Fever (70.37%), Oral Candidiasis (22.2%), Pulmonary Tuberculosis (11.11%) and Generalized Lymphadenopathy (18.51%) were significant predictors in present study. High risk behaviour of parents (37.30%) and mother’s HIV positivity (62.92%) were significant high risk factors, however needle prick (18.5%) was also equally significant in present study. Conclusions: Children brought with various signs and symptoms of HIV or born to high risk behaviour practicing parents and/or HIV positive mother, physician must get their patients tested for HIV (as per NACO Guidelines) so that infected children diagnosed early and referred to a specialized centre for treatment and follow up.